Democracia digital e deliberação on-line: uma análise do aproveitamento das discussões realizadas no portal e-democracia da Câmara Federal dos Deputados - Costa, Nayron Coelho Da (2015)
This paper analyzes the content developed within the discussion forums in virtual spaces available through the Federal House of Representatives e-Democracy website. That website offers citizens the opportunity to participate in drafting the text of laws, held by offering participatory tools such as chats, polls, collaborative text editors, in addition to discussion forums, space in which the research is concentrated. From this possibility of interaction between civil society and the government, and theoretical developments on the political participation undertaken through the Internet, the dissertation proposes, first, evaluate the degree of deliberativeness of online discussions held, using the justification, reciprocity, reflexivity, information and plurality indicators, taken from the deliberative theory literature. It also proposes to identify the demands of the participants originated from discussions in the forums and measure its use in the text of the enacted laws. Finally, the study seeks to establish a relationship between these two steps: a deliberative discussion and the use of the demands presented.